2006
DOI: 10.1007/s11104-005-1578-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu Toxicity on Growth of Cowpea (Vigna unguiculata)

Abstract: Accurate determination of the rhizotoxicity of Cu in dilute nutrient solutions is hindered by the difficulty of maintaining constant, pre-determined concentrations of Cu (micromolar) in solution.The critical Cu 2+ activity associated with a reduction in the growth of solution-grown cowpea (Vigna unguiculata (L.) Walp. cv Caloona) was determined in a system in which Cu was maintained constant through the use of a cation exchange resin. The growth of roots and shoots was found to be reduced at solution Cu 2+ act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
61
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 36 publications
12
61
1
3
Order By: Relevance
“…These observations are in general agreement with those reported for Ni toxicity in white clover, ryegrass, and cabbage (Yang et al 1996), tomato (Lycopersicon esculentum L.) (Palacios et al 1998), and fenugreek (Parida et al 2003). Interestingly, although the primary site of Ni 2+ toxicity in cowpea appears to be the shoot, the primary site of Pb 2+ and Cu 2+ toxicity in cowpea appears to be the root Kopittke and Menzies 2006). Nevertheless, all three trace metals have been shown to have a markedly similar influence on cowpea tissue nutrient concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These observations are in general agreement with those reported for Ni toxicity in white clover, ryegrass, and cabbage (Yang et al 1996), tomato (Lycopersicon esculentum L.) (Palacios et al 1998), and fenugreek (Parida et al 2003). Interestingly, although the primary site of Ni 2+ toxicity in cowpea appears to be the shoot, the primary site of Pb 2+ and Cu 2+ toxicity in cowpea appears to be the root Kopittke and Menzies 2006). Nevertheless, all three trace metals have been shown to have a markedly similar influence on cowpea tissue nutrient concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore concluded that the primary site of Ni 2+ toxicity in cowpea is in the shoots, with the observed reduction in root mass possibly the result of a decrease in the translocation of carbohydrates to the roots as suggested by Baccouch et al (1998). This is in contrast to that reported in cowpea for Cu 2+ toxicity (Kopittke and Menzies 2006) and Pb 2+ toxicity , where the root was considered to be the primary site of toxicity.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore Cu is required for the protein components of several enzymes 32 but in excess quantities, it is highly toxic to plant growth, resulting in complete inhibition of growth. 33 Our present study also resulted the less content of Cu in the raw HA plant sample than Fe and Zn which may reduce the accumulation of toxic substances like Ni, Cd, Cr and Pb which are well known heavy metals in soils for their cumulative accumulation and adverse effect on plant health. Macroscopy and Microscopy are the preliminary step for the standardization and based on that arrangement of anatomical structures are identified which further revealed the plant species identification.…”
Section: Resultssupporting
confidence: 56%
“…Guideline and threshold values chosen for further field data set analysis were selected by relative proximity to the field sample sites (UK), placing priority on use of the UK ICRCL information followed by EU information. References: [28][29][30][31][32][33][34][35]. Note: all values are mg/kg of dry weight sediment or soil.…”
Section: Deposited Sediment Contaminant Concentrationsmentioning
confidence: 99%